Comparative Life Cycle Assessment of Retort Pouch and Aluminum Can for Ready-to Bean Packaging - Gulcimen, Sedat; Ozcan, Ozlem; Cevik, Selin Babacan; Kahraman, Kevser; Uzal, Nigmet (Springer, 2023)
Since packaging contributes to severe environmental impacts in food production, alternatives of packaging materials that satisfy customer needs while minimizing environmental impacts in a cost-effective manner should be preferred for food product sustainability. This paper compares two different packaging materials (aluminum cans and retort pouches) with a life cycle approach to assess the environmental impacts of ready-to-eat bean packaging. The life cycle assessment (LCA) was used to define and compare the environmental performance of ready-to-eat beans in aluminum cans and retort pouches. The gate-to-gate approach was used in the LCA, with a functional unit of 1 kg of packaged ready-to-eat bean product. Inventory for packaging in retort pouch was created in collaboration with Duru Bulgur Company (Karaman, Turkey) and the data for ready-to-eat beans in the aluminum can were gathered from the literature. The findings show that ready-to-eat beans in retort pouches have lower environmental impacts than ready-to-eat beans in aluminum cans. The packaging and washing processes for both ready-to-eat beans packaged in aluminum cans and retort pouches had the greatest environmental impact. In ready-to-eat beans production, retort pouch provides 87% better environmental performance than aluminum can in terms of global warming (GW). Overall, the results demonstrated that replacing aluminum cans with retort pouches in ready-to-eat bean production can significantly reduce environmental effects in all impact categories. [Graphics] .
Keywords: Food Packaging; Life Cycle Assessment; Ready-to-Eat Bean; Retort Pouch; Aluminum Can